1968
DOI: 10.1029/jb073i006p02119
|View full text |Cite
|
Sign up to set email alerts
|

Marine magnetic anomalies, geomagnetic field reversals, and motions of the ocean floor and continents

Abstract: This paper summarizes the results of the three previous papers in this series, which have shown the presence of a pattern of magnetic anomalies, bilaterally symmetric about the crest of the ridge in the Pacific, Atlantic, and Indian oceans. By assuming that the pattern is caused by a sequence of normally and reversely magnetized blocks that have been produced by sea floor spreading at the axes of the ridges, it is shown that the sequences of blocks correspond to the same geomagnetic time scale. An attempt is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
170
1
1

Year Published

1970
1970
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,109 publications
(180 citation statements)
references
References 24 publications
8
170
1
1
Order By: Relevance
“…Heirtzler et al [7] have shown that, during the last 80 my, there has been about as much time when the geomagnetic field has a positive polarity as a negative polarity. Thus, an asymmetri~d histogram indicates a predominance of sources of one polarity whereas a symmetrical histogram indicates a probable equality between sources of positive and negative polarity and is compatible with a distribution of anomalies according to the Vine and Matthews model.…”
Section: E Le Borgne Aeimentioning
confidence: 99%
“…Heirtzler et al [7] have shown that, during the last 80 my, there has been about as much time when the geomagnetic field has a positive polarity as a negative polarity. Thus, an asymmetri~d histogram indicates a predominance of sources of one polarity whereas a symmetrical histogram indicates a probable equality between sources of positive and negative polarity and is compatible with a distribution of anomalies according to the Vine and Matthews model.…”
Section: E Le Borgne Aeimentioning
confidence: 99%
“…There is still disagreement among investigators about the number, Fig. 9 Geomagnetic time scale in column C is that inferred from the magnetization of three sediment cores (D, E, and F) and time scale inferred from magnetic anomalies (column A after Heirtzler et al, 1968, and column B after Pitman and Heirtzler, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Heirtzler, et al, (1968) have attempted to find an ocean area where the spreading has apparently been constant in time and in that area extrapolate the time scale to obtain a history of reversals as far as marine data will allow (see If it is assumed that a body width of one-tenth the depth of water could be detected by a sea level magnetic instrument then a body of about 0.3 km wide could conceivably be detected in many ocean areas. If this body is due to material spreading at a rate of 6 cm/yr then the magnetized body would correspond to an event of about 5,000 years duration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plate circuit Tanya needed stepped from the Pacific to the Antarctic to the Indian (because the Southwest Indian Ridge between the Antarctic and African plates was poorly known) to the African to the North American plate. The basic methodology was laid down by Jason (Atwater and Menard 1970), numbered according to the Heirtzler et al (1968) time scale as calibrated by Berggren (1969). Morgan (1968) and had immediately been taken up by Xavier Le Pichon at Lamont, who alone recognized its significance and single-handedly achieved the first self-consistent global circuit model, involving six plates, before the magnetic polarity time scale was resolved (Le Pichon 1968).…”
mentioning
confidence: 99%